Pelestarian Tradisi diba’iyyah Guna Menanamkan Rasa Cinta Rasul Pada Remaja Putri Dusun Bukaan Keling Kepung Kediri - Mudrikatul Falakhiyah; Rohmad Muzakki (LP3M IAIFA Kediri, 2020)
Seeing the current state of the modern, which with it causes many young millennials who forget the cultural traditions in the area where they live. Especially when it comes to religious culture. Therefore, the program of tradition was held inba'iyah to instill the love of the Apostle which contained many religious values. The preservation activities can be carried out properly, because of the participation of many parties, from the members, and the support of the community and parents in the village of Bukaan Keling Kepung. So that these activities can run successfully in instilling the love of the Apostle in today's young women. The number of members who have the willingness to follow this activity or program is evidence of the success of the preservation of the tradition. The success of this program can also be used as a program to implement the preservation of traditions elsewhere, which is in accordance with the context of each region.